Cell capacitor sizing in multilevel converters: cases of the modular multilevel converter and alternate arm converter - Merlin,MMC; Green,TC (IET Power Electronics, 2015)
Multilevel converters, such as the modular multilevel converter (MMC) or the alternate arm converter (AAC), rely on charged capacitors in their cells to generate their AC voltage waveform. Since the cell capacitors are physically large and occupy approximately half the cell volume, their capacitance must be kept minimal while limiting the voltage fluctuation caused by the current passing periodically through these capacitors. This study proposes a mathematical model which estimates the energy deviation for the stacks of both the MMC and the AAC during steadystate operation under any power factor and for AC voltage magnitude fluctuation of up to ±10%. The analysis is then used to calculate the minimum size for the cell capacitors in order to keep their voltage fluctuation within set boundaries for both topologies. The results show that the MMC requires 39 kJ/MVA of capacitive energy storage under sinusoidal modulation but this reduces with triplen injection modulation. The AAC has a lower requirement for storage in its cells of 11 kJ/MVA but the AAC has a sixpulse DC current ripple which requires a filter estimated to have a further 33% capacitive storage.